Human Resource Management Strategy in Permanent Nurseries in the Ministry of Environment and Forestry of the Republic of Indonesia : (Case Study in Six Permanent Nursery Locations of the Ministry of Environment and Forestry, West Java Province) - S. Siregar, Bernardus Wishman; Wibowo; Gustari, Irvandi (OGZ Research & Publishing, 2024)
The main focus in evaluation is aspects such as policy foundations, program support, implementation processes, and success of HR programs